Framing Media Berita Tempo VS Media Indonesia dalam Kasus Korupsi Pertamina: Kajian Norman Fairclough - Lina Yuliasari; Adel Lia Novita Sari (Linguistik, Terjemahan, Sastra (LINGTERSA), 2025)
The Pertamina corruption case has successfully captured the attention of the public, leading to frequent media coverage through online news with various framings that influence public perception. This research aims to investigate the framing of news regarding the Pertamina corruption case from the media Tempo and Media Indonesia using Fairclough’s model. The data sources used are online news articles from Tempo and Media Indonesia related to the Pertamina corruption case. The data collected includes words, phrases, and sentences within the news texts related to the Pertamina corruption case in online news from Tempo and Media Indonesia. The method employed in this study is qualitative descriptive. This research uses Norman Fairclough’s (1995) critical discourse analysis theory, which emphasizes three discourse dimensions. The results of this study indicate differences in framing between the two news media in the Pertamina corruption case. Tempo media framing builds a broader context by connecting the impact of Pertamina corruption in the economic sector, while Media Indonesia framing focuses on specific events with official statements without providing a broader context.